2018
DOI: 10.4236/jfcmv.2018.61002
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Behavior of Cavitation Cloud Shedding in Submerged Water Jets Issuing from a Sheathed Pipe Nozzle

Abstract: The behavior of cavitation cloud shedding in submerged water jets issuing from a sheathed pipe nozzle is investigated experimentally by high-speed camera visualization observation. Experiments are carried out under different cavitation numbers decreased to 0.01 with increase of the injection pressure, and the frequency spectrum of cavitation cloud shedding is evaluated by statistical analysis of a sequence of high-speed camera images. Experiments demonstrate that cavitation clouds appear when the cavitation nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The average gray level of a focused cylindrical area of 𝑅𝑅/𝑑𝑑 = 10 taken from the sheath exit to 𝑋𝑋′/𝑑𝑑 = 20 is evaluated and the temporal variation of the average grey level is investigated. Then, the dominant frequency 𝑓𝑓 of the average grey level variation is calculated by FFT transformation (Peng et al, 2018). As a dimensionless index for the unsteady periodicity Strouhal number St is defined by the following formula.…”
Section: Periodic Characteristics Of Air Layer Pulsationmentioning
confidence: 99%
“…The average gray level of a focused cylindrical area of 𝑅𝑅/𝑑𝑑 = 10 taken from the sheath exit to 𝑋𝑋′/𝑑𝑑 = 20 is evaluated and the temporal variation of the average grey level is investigated. Then, the dominant frequency 𝑓𝑓 of the average grey level variation is calculated by FFT transformation (Peng et al, 2018). As a dimensionless index for the unsteady periodicity Strouhal number St is defined by the following formula.…”
Section: Periodic Characteristics Of Air Layer Pulsationmentioning
confidence: 99%
“…Keiichi Sato et al [27] carried out a high-speed photographic study on the cavitation jet of a contraction expansion nozzle, and also obtained the low-frequency and high-frequency signals corresponding to the pressure fluctuation of the piston pump and the shedding of the cavitation group through the statistics of the change in cavity length over time. Peng G et al [28][29][30] used acrylic resin to make a transparent contraction nozzle, took a high-speed video of the cavitation distribution inside the nozzle and at the exit, and extracted the gray value of the image to obtain high-frequency and low-frequency signals respectively. By comparison, it was found that the low-frequency signal was consistent with the pulsation of the piston pump, while the high-frequency signal corresponded to the shedding frequency of the cavitation mass.…”
Section: Introductionmentioning
confidence: 99%
“…A transparent shrink-type nozzle using acrylic resin is used to observe the internal cavitation of the high-pressure jet nozzle, and high-frequency and low-frequency signals are obtained from the image grayscale of the high-speed photography [25]. By comparison, it is found that the low-frequency signal is consistent with the pulsation of the plunger pump, and the high-frequency signal is related to the frequency of the cavity shedding.…”
Section: Introductionmentioning
confidence: 99%